Corn Yield Response to the Use of a Nitrification Inhibitor with Anhydrous Ammonia - F. D. Hansel; D. A. Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2019)
Nitrification inhibitors are used to delay the nitrification process, reducing nitrogen (N) loss. The increase of nitrogen fertilization efficiency could promote greater corn grain yields and reduce environmental losses. The objective of this study was to evaluate corn response to the use of a nitrification inhibitor in corn grain. The study was carried out at four locations (Manhattan, Scandia, Rossville, and Ashland, KS) during 2017 and 2018 crop seasons. There was corn response to N fertilization, but no differences in corn yield were observed when anhydrous ammonia was treated with nitrification inhibitor at these site-years.
Keywords: corn yield; nitrogen fertilization; nitrification